2014
DOI: 10.4068/cmj.2014.50.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Intermediate-Supine Percutaneous Nephrolithotomy: Initial Experience

Abstract: We evaluated the feasibility and efficacy of intermediate-supine percutaneous nephrolithotomy (PCNL) in patients with renal calculi. Fifteen patients were included in this study. The intermediate-supine operative position was modified by using a 1-L saline bag below the ipsilateral upper flank. A nephrostomy and stone extraction were performed as usual. After completion of the stone removal, a nephrostomy tube was used when necessary according to the surgeon's decision. If there was no significant bleeding or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Other studies reported mean operative times ranging between 67.1±19.2 and 78.93±3.8 minutes with tubeless supine PCNL. [20,21] In our study (Table 4) only 2 (3.7%) patients received blood transfusion which is comparable to available literature indicating requirement for blood transfusion in 2.5-4% of the relevant patients. [12,20] Regarding Two (3.7%) patients developed complication of perinephric collection which was managed conservatively.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies reported mean operative times ranging between 67.1±19.2 and 78.93±3.8 minutes with tubeless supine PCNL. [20,21] In our study (Table 4) only 2 (3.7%) patients received blood transfusion which is comparable to available literature indicating requirement for blood transfusion in 2.5-4% of the relevant patients. [12,20] Regarding Two (3.7%) patients developed complication of perinephric collection which was managed conservatively.…”
Section: Discussionsupporting
confidence: 87%
“…Anesthesiologists prefer the supine position because of better airway control during procedures. Another advantage of the supine position is that there is no need for position changes when performing additional endoscopic procedures, such as cystoscopic or ureteroscopic operations [ 38 ]. Endoscopic combined intrarenal surgery is also a novel way of performing PCNL in the supine position [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean (SD) operative time was 91.33 (6.40) minutes (range: 80-105 minutes). Chung et al reported a mean operative time of 78.93 +/- 3.8 minutes [ 10 ]. De Sio et al reported a mean operative time of 43 minutes (range 25-120 minutes) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%